(untitled) (Medico Legal Update, 2020)
The aim of this study was to investigate the antibacterial activity of Lymnaea auricularia (snail) tissue powder and shell powder against different human pathogenic bacteria (Escherichia Coli, Pseudomonas aeruginoa and Klebsiella pneumonia). Four concentration was tested (75,100.125,150) mgof the powder with well diffusion assay. The highest activity of shell powder was in E. Coli at 75mgconcentration(19mm) inhibition zone, while the highest activity of tissue powder was in P. aeruginoa at 150mgconcentration with inhibition zone (28 mm). The powder extracts ‘ antimicrobial activity reveals that they may have biologically active metabolites.